Permeability Study of Several Soil Types in Kwala Bekala Field Trials USU Through Laboratory and Field Test - Nanda Akbar Siregar; Sumono Sumono; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Permeability of the soil is one of the important factor in designing drainage channels. The difference in the value of the permeability of the soil in the laboratory and in the field is due to of the different conditions in the test procedure. This study was aimed to determine the value of the rate of soil permeability on Andepts, Inceptisol, and the Ultisol through laboratory and field testing. Results of laboratory studies showed the value of the permeability rate was 1.34 cm/h at Andepts, 3.20 cm/h at g Inceptisol, and 1.06 cm/h at Ultisol. The field results showed that value of the permeability rate was 1.26 cm/h at Andepts, 2.23 cm/h at Inceptisol, and 0.98 cm/h at Ultisol. Factors affecting the value of the permeability differences among the three types of ground, among others, were the depth and the effective porosity of the soil. Difference in the value of soil permeability results in the laboratory and in the field was because of the thickness of the soil. Key Words: Permeability, Effective Depth, Porosity, Drainage.